Effect of fertilizers on the biomass production of Moringa oleifera and on some soil indicators during the establishment - Lok, Sandra; Suárez, Y. (Cuban Journal of Agricultural Science, 2016)
The performance of some morphological and productive indicators of Moringa oleifera related to compost application, chemical fertilization and bio-fertilizers, was determined, and the effect of this crop during its establishment on soil fertility was evaluated. The research was carried out in the Institute of Animal Science. A random block design was used, with four replications and seven treatments, in a red ferrallitic soil. The fertilization treatments were: T1 = control; T2 = bovine manure (25 t ha-1); T3 = bovine manure (25 t ha-1) + Fitomas E; T4 = bovine manure (25 t ha-1) + EcoMic; T5 = bovine manure (25 t ha-1) + EcoMic®+ Fitomas E; T6 = NPK (60:90:160; 0.6 t ha-1) and T7 = NPK (60:90:160; 0.3 t ha-1) + EcoMic +Fitomas E. Height, number of branches, number of leaves, stem diameter, population and yield of DM ha-1 of plants were determined. In the soil, the contents of N, P, Ca, Mg, pH and OM were evaluated. The Supergenius accession under edaphoclimatic and handling conditions, similar to those of the research, should reach a height of 1 m and 35 leaves per branch at 60 days, approximately. Treatment T4 showed the best biomass production (6.61 t DM ha-1) and the highest contribution to the improvement of nutrient contents of soil (P: 136.56 p.p.m.; Ca: 1.89%; Mg: 0.38% and OM: 4.84%). It can be concluded that the application of 25 t ha-1 of bovine manure and EcoMic showed the highest yield of moringa and the best contribution to nutrient contents of soil, while the application of compost, with bio-fertilizers or without them, had better effect on soil fertility than the application of inorganic fertilizer, alone or combined, because it influenced positively on all the nutrients of soil. It is recommended to continue research related to the application of fertilizers on moringa sowing, as well as other related to the effect of this plant on soil fertility, with different times of their exploitation and for other accessions. Key words: productivity, forage, biomass, soil fertility, fertilization